Collaboration Of Consumer Resources For Service Innovation In Social E-Commerce: The Effects Of Social Media Influencer Mediation - Ni Rai Artini; Aripin, Zaenal Aripin; Pynatih, Ngurah Made Novianha (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The rapid growth of social e-commerce has transformed the online commerce landscape, driving significant changes in consumer behavior. Consumer resource collaboration is becoming increasingly important in this context, enabling brands to expand reach and accelerate service innovation. On the other hand, the influence of social media influencers is increasingly strengthening the role of consumers in influencing purchasing decisions and creating trends. This research aims to investigate the role of consumer resource collaboration in driving service innovation in social e-commerce, by considering the mediating effect of social media influencers. The research approach used is qualitative by analyzing data from related journals, articles and books. The research involved a survey of respondents involved in social e-commerce, as well as in-depth interviews with social media influencers involved in collaborations with brands. The research results show that consumer resource collaboration has a significant impact in expanding brand reach, increasing consumer engagement, and accelerating the adoption of innovations in social e-commerce. Social media influencer mediation has also been proven to strengthen consumer influence in influencing purchasing decisions and creating greater brand awareness.